Wide-range and sensitive detection of LPS using a transporter@liposome enhanced electrochemical aptasensor - Xinyu Hu; Shukai Song; Ruyu Lin; Weidong Zheng; Haochen Qi; Lin Xu; Jian Zhang (Analytica Chimica Acta, 2026)

Lighting up the Arctic: Nighttime light data reveals economic growth in the north in Norway, Sweden and Finland - Zhenfu Li; Haochen Yu; Chunrui Song; Xinli Qi; Qiqi Zhang (Polar Science, 2026)

Research on expansion of hydraulic fractures based on reservoir architecture: implications for well spacing in the northern Ordos Basin tight gas reservoir - Lei Bao; Qi Chen; Yuming Liu; Haochen Liu; Minghao Zhao; Xinqiang Liu; Jiagen Hou (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Insight into poplar fractionation enhancement via an eco-manufacturing process using sulfonated magnetic polystyrene solid acid and biphasic solvent - Haochen Du; Cuiyi Liang; Shijun Liu; Xuesong Tan; Yang Chen; Shiyou Xing; Yu Zhang; Wei Liu; Wen Wang; Xin Shi; Zhongming Wang; Wei Qi (Chemical Engineering Journal, 2026)

Characterization of Interlayer Resistivity Responses in Crack-Containing Rock-Like Materials and Analysis of Failure Precursors - Tingye Qi; Hongtao Xu; Guorui Feng; Tian Qiu; Haochen Wang; Linfei Wang; Siyuan Cheng; Xinkai Qi; Lubin Li (Rock Mechanics and Rock Engineering, 2026)

Evolutionary game analysis of pirate attack based on prospect theory - Zhenfu Li; Haochen Yu; Xinli Qi; Chunrui Song; Wei Duan; Shiyue Li (Frontiers in Marine Science, 2026)
Pirate attacks are related to shipping safety, international trade order, and regional political stability. How to effectively address this problem has become a pressing issue that the international community needs to tackle urgently. This study constructs a three-player evolutionary game model involving shipping companies, pirates, and the government. It analyzes the strategic evolution and interaction mechanisms of each subject in the context of pirate attacks. Based on prospect theory, this study employs MATLAB simulation experiments and sensitivity analysis to investigate the impact of subjective factors, such as risk aversion, on the strategic choices of each player. The results show that: (1) The key to effectively curbing piracy is to increase the intensity of crackdowns on its crimes to reduce its illegal profit expectations; (2) Shipping companies show a strong risk aversion tendency in the game, and they tend to equip defensive equipment even if the probability of pirate attacks is very low; (3) The government’s perceived value sensitivity coefficient threshold is the highest. Only when it has a stronger risk perception and strategy adjustment capabilities can it adjust its escort policy promptly in response to pirate attacks. This study can provide theoretical support and decision-making reference for the formulation of quantitative representation of cross-border governance modesce policies.

Spatiotemporal variability of soil moisture and its influencing factors in a forested catchment with complex terrain - Haochen Liu; Shangqiang Hui; Yuting Zhao; Yanjia Jiang; Yongliang Qi; Elizabeth W. Boyer; Carlos R. Mello; Li Guo; Hongxia Li (CATENA, 2025)

Arbuscular mycorrhizal fungi enhance glyphosate resistance in an invasive weed: Implications for eco-environmental risks - Shanshan Qi; Daiyi Chen; Mengting Yan; Zhiyun Huang; Haochen Yu; Guangqian Ren; Hu'anhe Xiong; Wei Fu; Biying Zhao; Zhicong Dai; Daolin Du; Torsten Thomas (Applied Soil Ecology, 2025)

In-situ constructed ZnAl2O4/A-MoS2 Z-scheme heterojunction for visible-light-thermo cascade catalytic CO2 cycloaddition - Congcong Zhang; Bin Jiang; Runjia Mou; Haochen Shen; Qi Zhou; Longfei Zhang; Jingshuai Li; Na Yang; Luhong Zhang (Journal of Environmental Chemical Engineering, 2025)

A disposable microfluidic aptasensor for one-step and real-time detection of sub-femtomolar-level aflatoxin B1 in food - Haochen Qi; Jian Zhang; Xueyong Zhang; Li Lv; Tianqi Wang; Erhui Huang; Jayne Wu; Lei Zheng (Food Research International, 2024)

Highly efficient adsorption of ciprofloxacin from aqueous solutions by waste cation exchange resin-based activated carbons: Performance, mechanism, and theoretical calculation - Qiang Li; Haochen Li; Xiaofei Zong; Haochao Sun; Yunhao Liu; Ziyi Zhan; Shou Mei; Yanjie Qi; Yangbo Huang; Yuxuan Ye; Fei Pan (Science of The Total Environment, 2024)

An artificial neural network-based machine learning approach to correct coarse-mesh-induced error in computational fluid dynamics modeling of cell culture bioreactor - Fernando José Cantarero-Rivera; Ran Yang; Haochen Li; Hairong Qi; Jiajia Chen (Food and Bioproducts Processing, 2024)

Recognizing iso-olefins as paramount intermediates for optimum isoparaffins production via CO hydrogenation - Haochen Qi; Cederick Cyril Amoo; Wuqiang Si; Jian Lou; Xuangan Liu; Chunyang Zeng; Qingjie Ge; Jian Sun; Chuang Xing; Xinhua Gao (Fuel, 2023)

Life cycle environmental benefits of recycling waste liquor and chemicals in production of lignocellulosic bioethanol - Yunzi Hu; Haochen Du; Luyao Xu; Cuiyi Liang; Yu Zhang; Zhigang Sun; Carol Sze Ki Lin; Wen Wang; Wei Qi (Bioresource Technology, 2023)

One-step and real-time detection of Hg2+ in brown rice flour using a biosensor integrated with AC electrothermal enrichment - Haochen Qi; Lei Xiao; Jayne Wu; Li Lv; Xinyu Hu; Youyi Zhuang; Xiaoru Liu; Wenci Zhao; Fangshuo You; Jian Zhang; Lei Zheng (Food Chemistry, 2023)

A novel economic benefit calculation modeling applying to coal mining - Zhicheng Zhang; Qi Ding; Guorui Feng; Tingye Qi; Yanyu Guo; Yiwen Wang; Haochen Wang; Xinyu Gao (Environment, Development and Sustainability, 2023)

Life cycle assessment in urban territories: a case study of Dalian city, China - Yu Qi; Yun Zhang; Hui Jiang; Haochen Hou; Jinhua Li (The International Journal of Life Cycle Assessment, 2019)

Life cycle assessment and optimization analysis of different LNG usage scenarios - Yun Zhang; Hui Jiang; Jinhua Li; Shuai Shao; Haochen Hou; Yu Qi; Shushen Zhang (The International Journal of Life Cycle Assessment, 2018)